2021
DOI: 10.1108/ijpdlm-12-2020-0450
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain risk mitigation strategies during COVID-19: exploratory cases of “make-to-order” handloom saree apparel industries

Abstract: PurposeThis study attempts to identify the supply chain risks (SCRs) induced during the COVID-19 disruption in an Indian handloom saree industry and determine suitable risk mitigation strategies (RMSs) to overcome the impact of the epidemic disruption.Design/methodology/approachThis work determined 11 SCRs through an extensive literature review in the context of the handloom apparel industry and validated through the experts. Further, a multiple case-based approach is used in this research. Within case and cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 53 publications
0
51
0
2
Order By: Relevance
“…As the nature of disasters and their induced risk to supply chains is different, the nature of barriers posed by the different disasters can be different (Cozzolino, 2012 ; Dohale et al, 2021 ; Dohale, Ambilkar, et al, 2021 ; Dohale, Gunasekaran, et al, 2021 ; Dohale, Gunasekaran, et al, 2021 ; Dohale, Verma, et al, 2021 ; Dohale, Verma, et al, 2021 ). Pandemics are the unique kind of disasters that creates a negative impact on a massive multi-country or worldwide scale, which may or may not be observed during natural disaster (Dora & Kumar, 2020 ; Thompson & Anderson, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As the nature of disasters and their induced risk to supply chains is different, the nature of barriers posed by the different disasters can be different (Cozzolino, 2012 ; Dohale et al, 2021 ; Dohale, Ambilkar, et al, 2021 ; Dohale, Gunasekaran, et al, 2021 ; Dohale, Gunasekaran, et al, 2021 ; Dohale, Verma, et al, 2021 ; Dohale, Verma, et al, 2021 ). Pandemics are the unique kind of disasters that creates a negative impact on a massive multi-country or worldwide scale, which may or may not be observed during natural disaster (Dora & Kumar, 2020 ; Thompson & Anderson, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recently, the COVID-19 pandemic has disrupted the supply chain network worldwide, resulting in substantial business and economic losses globally, and took away millions of lives (Dohale, Ambilkar, et al, 2021 ; Dohale, Gunasekaran, et al, 2021 ; Dohale, Verma, et al, 2021 ). As reported by World Bank, the global GDP could observe the contraction of 5.2% and stated it as the “deepest global recession in decades” (World Bank, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, only a limited number of studies have explored the ways in which organisations can mitigate the impact of SCDs caused by the COVID-19 pandemic (Butt 2021;Dohale et al 2021;El Baz and Ruel 2021;Mahajan & Tomar 2021). Dohale et al (2021) and Mahajan and Tomar (2021) conducted extensive literature reviews to recontextualise previously identified SCDs within the context of the COVID-19 pandemic.…”
Section: Supply Chain Disruption Managementmentioning
confidence: 99%
“…To date, only a limited number of studies have explored the ways in which organisations can mitigate the impact of SCDs caused by the COVID-19 pandemic (Butt 2021;Dohale et al 2021;El Baz and Ruel 2021;Mahajan & Tomar 2021). Dohale et al (2021) and Mahajan and Tomar (2021) conducted extensive literature reviews to recontextualise previously identified SCDs within the context of the COVID-19 pandemic. Butt ( 2021) conducted a qualitative study to explore importing disruptions experience by manufacturing organisations, whilst El Baz and Ruel ( 2021) investigated the role of risk-mitigating strategies in French firms' responses to the pandemic.…”
Section: Supply Chain Disruption Managementmentioning
confidence: 99%
See 1 more Smart Citation